Y Inang Prihatina Inspirasi Kerang Pada Busana Pesta Menggunakan Tenun Dan Slashing - Subagyo, Alma Primadora; Prihatina, Yuhri Inang (BAJU: Journal of Fashion and Textile Design Unesa, 2024)
The purpose of this study was to determine the manufacturing process and finished results of seashell inspiration in party fashion using slashing and men's clothing using screen printing. Inspired by shells because it has a philosophy that can be applied in life. Shells from a visual point of view have a unique symmetrical and connected shell shape so that it is interesting to be used as a source of ideas in making fashion works. Jepara torso woven fabric was chosen because it has traditional motifs and strong fabric properties in accordance with slashing techniques. Duchesse satin fabric was chosen to reinforce the glamorous impression of party attire. The method used in this study is double diamond. Includes 4 processes, namely discover, define, develope, and deliver. The shape of the distilled shells becomes a slashing motif on the torso jepara woven material into a skirt layer. The results of the Shell Inspiration in Party Clothing and Men's Clothing, in terms of design placement manipulating fabric, namely slashing in party clothes, and polyflex flock screen printing in men's clothing with seashell motifs make the center of interest in party clothing and men's clothing, and give a thick ethnic impression but do not leave a luxurious impression.